2016
DOI: 10.1111/bjd.14214
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocytes and neutrophils are important sources of proinflammatory molecules in hidradenitis suppurativa

Abstract: IL-17-producing cells are present in lesional and perilesional HS skin and may contribute to the initiation of inflammatory processes. Furthermore, the epidermis is a source of proinflammatory cytokines, shows inflammasome activation and expresses S100A8/S100A9, thereby possibly contributing to the propagation of inflammation. A massive influx of IL-17-expressing neutrophils is observed in the deep infiltrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
205
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(235 citation statements)
references
References 26 publications
(45 reference statements)
14
205
0
5
Order By: Relevance
“…We do not know the extent of their influence in the pathology of psoriasis or in comparison with other IL-17/IL-22 producing cell types but recent publications addressing the dermato-pathology in skin diseases such as hydradenitis suppurativa, Schnitzler’s syndrome and delayed-pressure urticaria suggest a broader role of neutrophil-produced IL-17 in skin inflammation 16,17 . Another aspect of IL-17 production by neutrophils in psoriatic inflammation is that neutrophils, comprising more than 50% of leukocytes in the blood and might contribute to the cardio metabolic co morbidities associated with severe psoriasis.…”
Section: To the Editormentioning
confidence: 99%
“…We do not know the extent of their influence in the pathology of psoriasis or in comparison with other IL-17/IL-22 producing cell types but recent publications addressing the dermato-pathology in skin diseases such as hydradenitis suppurativa, Schnitzler’s syndrome and delayed-pressure urticaria suggest a broader role of neutrophil-produced IL-17 in skin inflammation 16,17 . Another aspect of IL-17 production by neutrophils in psoriatic inflammation is that neutrophils, comprising more than 50% of leukocytes in the blood and might contribute to the cardio metabolic co morbidities associated with severe psoriasis.…”
Section: To the Editormentioning
confidence: 99%
“…A greater caspase-1 activity in the keratinocytes of the affected skin was also observed. 88 One therapy with colchicine, an effective medication in other diseases with inflammasomes, such as familial mediterranean fever and gout, was evaluated in eight patients with HS, but it proved not to be beneficial. 89 …”
Section: Dermatological Diseases Associated With Inflammasomesmentioning
confidence: 99%
“…It has been shown that interleukin-17 (+) cells are increased in lesional and perilesional skin of HS 10 11. These innate immune cells are involved in the inflammatory process of HS 10 11.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that interleukin-17 (+) cells are increased in lesional and perilesional skin of HS 10 11. These innate immune cells are involved in the inflammatory process of HS 10 11. The large number of infiltrating neutrophils, particularly during the advanced stages of disease, explains how HS can be included in the spectrum of neutrophilic dermatoses 11.…”
Section: Discussionmentioning
confidence: 99%